Predictors of continuation with olanzapine during the 1-year naturalistic treatment of patients with schizophrenia in Japan - Ye, Wenyu (Dove Medical Press, 2011)
PURPOSE: Treatment continuation is considered an important measure of antipsychotic effectiveness in schizophrenia, reflecting the medication’s efficacy, safety, and tolerability from both patients’ and clinicians’ perspectives. This study identified characteristics of patients with schizophrenia who continue olanzapine therapy for a 1-year period in Japan. METHODS: In a large (N = 1850), prospective, observational study, Japanese patients with schizophrenia who initiated treatment with olanzapine were followed for 1 year. Baseline characteristics were compared using t-tests and chi-square tests. Stepwise logistic regression was used to identify independent baseline predictors of treatment continuation. RESULTS: Most patients (68.2%) continued with olanzapine therapy for the full 1-year study period, with an average duration of 265.5 ± 119.4 days. At baseline, patients who continued were significantly more likely to be male, older, and inpatients; have longer illness duration, higher negative and cognitive symptoms, better health-related quality of life, and prior anticholinergic use. Continuers were significantly less likely to engage in social activities, live independently, work for pay, or have prior antidepressant use. Continuers showed significantly greater early (3-month) improvement in global symptom severity. Logistic regression found that continuation was significantly predicted by longer illness duration, lower positive symptoms, higher negative symptoms, and better health-related quality of life. CONCLUSIONS: In this large naturalistic study in Japan, most patients with schizophrenia stayed on olanzapine therapy for the full 1-year study period. Treatment completion with olanzapine was independently predicted by longer illness duration, lower positive symptoms, higher negative symptoms, and better health-related quality of life.